2018
DOI: 10.1111/jth.13951
|View full text |Cite
|
Sign up to set email alerts
|

Citrullinated histone H3, a biomarker of neutrophil extracellular trap formation, predicts the risk of venous thromboembolism in cancer patients

Abstract: Background Neutrophil extracellular traps (NETs) are decondensed chromatin fibers that might play a role in the prothrombotic state of cancer patients. Objectives To investigate whether the levels of citrullinated histone H3 (H3Cit), a biomarker for NET formation, cell-free DNA (cfDNA) and nucleosomes predict venous thromboembolism (VTE) in cancer patients. Patients/Methods Nine-hundred and forty-six patients with newly diagnosed cancer or progression after remission were enrolled in this prospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
182
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(192 citation statements)
references
References 48 publications
(57 reference statements)
6
182
1
3
Order By: Relevance
“…Additionally, we investigated the association of NETs and the risk of mortality in patients with cancer. In conformity with previous studies we quantified NETs by measuring plasma levels of biomarkers reflecting NET formation, H3Cit, cfDNA and nucleosomes (Demers et al , ; Martinod et al , ; Thålin et al , ; Mauracher et al , ).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…Additionally, we investigated the association of NETs and the risk of mortality in patients with cancer. In conformity with previous studies we quantified NETs by measuring plasma levels of biomarkers reflecting NET formation, H3Cit, cfDNA and nucleosomes (Demers et al , ; Martinod et al , ; Thålin et al , ; Mauracher et al , ).…”
supporting
confidence: 57%
“…Experimental studies suggest that tumours pre‐dispose neutrophils to release NETs, which then induce a prothrombotic state (Engelmann & Massberg, ; Martinod & Wagner, ; Laridan et al , ; Pertiwi et al , ). The first evidence of a role of NETs for cancer‐associated VTE was reported recently in a study by Mauracher et al (), which found a 13% relative increase in VTE risk per 100 ng/ml increase in H3Cit level. In contrast, we did not observe an association of H3Cit with ATE in patients with cancer in our present study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Of note, we found that K s and CLT, as well as thrombin, generation were associated with H3Cit measured in vivo, a finding that supports several prothrombotic effects of NET formation among others observed after addition of DNA and histones to plasma and expands them by showing association between NET formation and prothrombotic fibrin clot structure and lysability after VTE. The current study provides new insights into association of NET formation with a hypercoagulable state that can be observed not only in cancer‐associated thrombosis but also in VTE patients with no clinically evident malignancy at the time of VTE. A diagnostic value of H3Cit in VTE patients in the context of cancer deserves further investigation.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, mouse studies demonstrated that NETs contribute to thrombosis in the IVC stenosis model [33, 60]. In terms of cancer-associated thrombosis, plasma citrullinated histone H3, a marker of NETs, is associated with venous thrombosis in cancer patients [61]. Further, mouse studies sought to determine the role of NETs in cancer-associated thrombosis.…”
Section: Neutrophil Extracellular Trapsmentioning
confidence: 99%